2013
DOI: 10.1017/s1461145712000752
|View full text |Cite
|
Sign up to set email alerts
|

The potent M1 receptor allosteric agonist GSK1034702 improves episodic memory in humans in the nicotine abstinence model of cognitive dysfunction

Abstract: Episodic memory deficits are a core feature of neurodegenerative disorders. Muscarinic M(1) receptors play a critical role in modulating learning and memory and are highly expressed in the hippocampus. We examined the effect of GSK1034702, a potent M(1) receptor allosteric agonist, on cognitive function, and in particular episodic memory, in healthy smokers using the nicotine abstinence model of cognitive dysfunction. The study utilized a randomized, double-blind, placebo-controlled, cross-over design in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 51 publications
6
89
1
Order By: Relevance
“…Recently, the M 1 mAChR allosteric agonist GSK1034702, an isomer of compound 44, has shown efficacy in improving episodic memory in humans in a nicotine abstinence model of cognitive dysfunction. 144 An 8 mg dose of GSK1034702 significantly improved immediate recall (but not delayed recall) following abstinence-induced impairment. Furthermore, in preclinical studies, the potency of GSK1034702 was sensitive to the M 1 mAChR F77I mutation, a mutation that also had a pronounced effect on the efficacy of AC-42 and 77-LH-28-1; suggesting a similar, potentially bitopic, binding mode.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 93%
“…Recently, the M 1 mAChR allosteric agonist GSK1034702, an isomer of compound 44, has shown efficacy in improving episodic memory in humans in a nicotine abstinence model of cognitive dysfunction. 144 An 8 mg dose of GSK1034702 significantly improved immediate recall (but not delayed recall) following abstinence-induced impairment. Furthermore, in preclinical studies, the potency of GSK1034702 was sensitive to the M 1 mAChR F77I mutation, a mutation that also had a pronounced effect on the efficacy of AC-42 and 77-LH-28-1; suggesting a similar, potentially bitopic, binding mode.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 93%
“…It has been reported that these new agents display antipsychotic drug-like qualities Ma et al, 2009), reverse scopolamine-induced memory deficits (Lebois et al, 2010) and potentiate CA1 hippocampal pyramidal cell firing, a physiological response associated with learning and memory (Bradley et al, 2010;Buchanan et al, 2010;Jones et al, 2008). In a pre-clinical human trial, Nathan et al (2013) examined the effects of GSK1034702, a potent M1 receptor allosteric agonist, on alleviating the symptoms of cognitive dysfunction amongst a group of, otherwise healthy, male smokers. Employing a nicotine-abstinence model of cognitive dysfunction, GSK1034702 was found to reduce impairments in information encoding by significantly increasing participants performance on measures of Table 1 Behavioural effects of xanomeline.…”
Section: Targeting the Muscarinic Systemmentioning
confidence: 99%
“…Importantly, clinical and preclinical studies suggest that cortical CHRM1 is important in cognitive functions (Anagnostaras et al, 2003;Nathan et al, 2012). Thus, in this study, we choose to expand our studies on cortical CHRM1 to BA6, a region that has been shown to act in concert with BA9 when cognitive tasks such as attention, working memory, episodic memory retrieval and visual awareness are being undertaken (Naghavi and Nyberg, 2005).…”
Section: Introductionmentioning
confidence: 99%